Thematic Structure and Thematic Progression in Research Articles Published in Scopus-Indexed International Journals - Endang Susilowati; Abdurrachman Faridi; Zulfa Sakhiyya (English Education Journal, 2022)
Publishing in highly-indexed journals is greatly competitive, thus writing a qualified and eligible text becomes more challenging for a second/foreign language writer of English. A good text should be written logically and organized effectively according to the role of good academic writing. Thematic structure and thematic progression contribute to the development of a well-structured meaningful text. This study examines the use of thematic structure and thematic progression in research articles published in Q1 and Q2 Scopus-indexed international journals as well as their relationship to achieve the texts’ coherence. This is a descriptive qualitative study within the framework of Systemic Functional Linguistics (SFL) that employs discourse analysis. 3426 clauses gathered from ten research articles were analyzed by using Halliday and Matthiessen’s (2014) taxonomy of thematic structure and Eggins’s (2004) theory of thematic progression. This study highlights three major findings. Firstly, in terms of thematic structure, the textual theme is massively used followed by the topical and interpersonal theme. The predominance of the textual theme implies the authors’ ability in developing the logical relations between clauses. Secondly, in terms of the thematic progression, the theme reiteration pattern is frequently employed, followed by the multiple-rheme and the zig-zag pattern. The tremendous use of the theme reiteration indicates the authors’ ability in maintaining the focus of the texts. Thirdly, the relationship between thematic structure and thematic progression constructs logical relations between the clauses to achieve the texts’ coherence. Finally, this study provides some pedagogical implications for the teaching of English as a second/foreign language.